PELAKSANAAN PEMBERIAN ASURANSI TERHADAP KORBAN KECELAKAAN LALU LINTAS OLEH PT. JASA RAHARJA DI KOTA PEKANBARU - Kristina, Nova; Bachtiar, Maryati; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Transportation has a very broad role and importance for the economicdevelopment of the nation. Developments in science and technology especially in thefield of traffic and transportation, it not only provides benefits and positive influenceon the behavior of people's lives, but it can also have negative impacts, such as theemergence of problems in areas such as traffic accidents.The government through the Law. 34 Year 1964 on Road Traffic AccidentFund provides insurance benefits for victims of traffic accidents, which in thisimplementation is left to the PT. Jasa Raharja (Persero). Duties and responsibilitiesare to collect funds from the public through donations compulsory motor vehicleowners are performed each year, and thereafter is channeled back to the communitythrough the insurance compensation to the victim or the victim's heirs, which aim toreduce the burden of costs due to road traffic accidents, which given the amount ofcompensation has been set in the Regulation of the Minister of Finance DecreeNo.36/PMK.010/2008 of Great Benefit and Contribution Compulsory Road TrafficAccident FundKeywords : Insurance, Road Traffic, Accidents